Effects of the cyclic and collective pitch variations on a wind-tunnel rotary-wing decelerator behavior - Martiarena, Juan Francisco (2021)
The effects of the cyclic and collective pitch variations on a rotating blade decelerator (pararotor) wind-tunnel behavior are studied. The dynamics and aerodynamics effects of the cyclic pitch variations were studied. Starting from the Newton Euler equations, a dynamic model of the main axis dynamics is obtained. The results confirm that the cyclic pitch variations of the blades are an effective way to modify the net force and torque on the pararotor, and consequently, could be used to control pararotors with low aspect ratio blades.